Inhibition of casein kinase 2 sensitizes mantle cell lymphoma to venetoclax through MCL-1 downregulation - Thus, Yvonne J.; De Rooij, Martin F.M.; Swier, Nathalie; Beijersbergen, Roderick L.; Guikema, Jeroen E.J.; Kersten, Marie-José; Eldering, Eric; Pals, Steven T.; Kater, Arnon P.; Spaargaren, Marcel (Haematologica (Roma), 2023)
BCL-2 family proteins are frequently aberrantly expressed in mantle cell lymphoma (MCL). Recently, the BCL-2-specific inhibitor venetoclax has been approved by the US Food and Drug Administration for chronic lymphocytic leukemia (CLL) and acute myeloid leukemia (AML). In MCL, venetoclax has shown promising efficacy in early clinical trials; however, a significant subset of patients is resistant. By conducting a kinome-centered CRISPR-Cas9 knockout sensitizer screen, we identified casein kinase 2 (CK2) as a major regulator of venetoclax resistance in MCL. Interestingly, CK2 is over-expressed in MCL and high CK2 expression is associated with poor patient survival. Targeting of CK2, either by inducible short hairpin RNA (shRNA)-mediated knockdown of CK2 or by the CK2-inhibitor silmitasertib, did not affect cell viability by itself, but strongly synergized with venetoclax in both MCL cell lines and primary samples, also if combined with ibrutinib. Furthermore, targeting of CK2 reduced MCL-1 levels, which involved impaired MCL-1 translation by inhibition of eIF4F complex assembly, without affecting BCL-2 and BCL-XL expression. Combined, this results in enhanced BCL-2 dependence and, consequently, venetoclax sensitization. In cocultures, targeting of CK2 overcame stroma-mediated venetoclax resistance of MCL cells. Taken together, our findings indicate that targeting of CK2 sensitizes MCL cells to venetoclax through downregulation of MCL-1. These novel insights provide a strong rationale for combining venetoclax with CK2 inhibition as therapeutic strategy for MCL patients.